Communication is key: Innate immune cells regulate host protection to helminths - Peng, Jianya; Federman, Hannah G.; Hernandez, Christina M.; Siracusa, Mark C. (Frontiers in Immunology, 2022)
Parasitic helminth infections remain a significant global health issue and are responsible for devastating morbidity and economic hardships. During infection, helminths migrate through different host organs, which results in substantial tissue damage and the release of diverse effector molecules by both hematopoietic and non-hematopoietic cells. Thus, host protective responses to helminths must initiate mechanisms that help to promote worm clearance while simultaneously mitigating tissue injury. The specialized immunity that promotes these responses is termed type 2 inflammation and is initiated by the recruitment and activation of hematopoietic stem/progenitor cells, mast cells, basophils, eosinophils, dendritic cells, neutrophils, macrophages, myeloid-derived suppressor cells and group 2 innate lymphoid cells. Recent work has also revealed the importance of neuron-derived signals in regulating type 2 inflammation and antihelminth immunity. These studies suggest that multiple body systems coordinate to promote optimal outcomes post-infection. In this review, we will describe the innate immune events that direct the scope and intensity of antihelminth immunity. Further, we will highlight the recent progress made in our understanding of the neuroimmune interactions that regulate these pathways and discuss the conceptual advances they promote.